2003
DOI: 10.1128/aem.69.11.6899-6907.2003
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Succession of Structure and Diversity of a Biofilm Formed in a Model Drinking Water Distribution System

Abstract: In this study, we examined the long-term development of the overall structural morphology and community composition of a biofilm formed in a model drinking water distribution system with biofilms from 1 day to 3 years old. Visualization and subsequent quantification showed how the biofilm developed from an initial attachment of single cells through the formation of independent microcolonies reaching 30 m in thickness to a final looser structure with an average thickness of 14.1 m and covering 76% of the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
147
2
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(174 citation statements)
references
References 39 publications
19
147
2
6
Order By: Relevance
“…Early colonizers might change the environmental conditions in the biofilm, e.g., by altering the substratum surface [16,18], and hence facilitating the attachment of filamentous cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early colonizers might change the environmental conditions in the biofilm, e.g., by altering the substratum surface [16,18], and hence facilitating the attachment of filamentous cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Successional community changes during the colonization of new habitats or after environmental disturbances have been described for communities of planktonic and benthic microalgae [12,24], and more recently in bacterial communities [9,14,18]. Primary succesional development of an ecosystem is always initiated by the settlement of pioneer organisms in a previously uncolonized environment.…”
Section: Introductionmentioning
confidence: 99%
“…DWDS bacterial community can be influenced by chlorine levels, concentration of organic compounds, water temperature, and physicochemical characteristics of pipe materials (Niquette et al, 2001). In addition, the occurrence of bacterial community succession was observed in a model DWDS (Martiny et al, 2003), demonstrating a long-term development of biofilm formation in DWDSs.…”
Section: Introductionmentioning
confidence: 97%
“…However, valuable information has been obtained from the laboratory or pilot reactors that simulate DWDSs. Examining community dynamics in an oligotrophic, disinfectant-free model system revealed that biofilm development on surfaces in contact with drinking water is slow and involves community succession over a multiyear span (Martiny et al, 2003). This study highlights the need for temporal replication for DWDS biofilm studies.…”
Section: Introductionmentioning
confidence: 99%